An intersectional analysis of social constraints and agency among sex workers in Tunisia during the COVID-19 pandemic; the community-based qualitative study EPIC-MENA - Marion Di Ciaccio; Elisa Adami; Nassima Boulahdour; Othmane Bourhaba; Juliana Castro Avila; Nicolas Lorente; Khawla Beldi Chouikha; Montassar Nabli; Sonia Torkhani; Mehdi Karkouri; Daniela Rojas Castro (Global Public Health)
The economic, social and health impacts of the COVID-19 pandemic varied across population groups. This study aimed to provide a comprehensive view of the effects of socioeconomic constraints on sex workers’ agency during the COVID-19 pandemic in Tunisia, using the analytical framework of intersectionality. We performed a thematic content analysis of semi-structured interviews conducted with sex workers (n = 19). Results highlighted the heavy burden of socioeconomic constraints on their agency, and specifically on their decision to continue sex work or not during the pandemic. The fact that there were fewer clients during the pandemic led to greater economic precarity, especially among mothers. Furthermore, interviewees – mostly cisgender male sex workers with same-sex practices – reported increased violence and discrimination by clients and the police. Participants also experienced difficulties accessing health care for themselves and for their children, including access to COVID-19 vaccination. This was especially true for women with a low educational level. Finally, sex workers’ mental health was also strongly affected by the pandemic. Findings highlights the role of various intersecting socioeconomic conditions and structural vulnerabilities on sex workers’ experience of the COVID-19 pandemic in Tunisia, in terms of health and their capacity to negotiate agency.